2013
DOI: 10.1371/journal.pone.0081712
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Candidate Serum Proteins for Classifying Well-Differentiated Small Intestinal Neuroendocrine Tumors

Abstract: BackgroundPatients with well-differentiated small intestine neuroendocrine tumors (WD-SI-NETs) are most often diagnosed at a metastatic stage of disease, which reduces possibilities for a curative treatment. Thus new approaches for earlier detection and improved monitoring of the disease are required.Materials and MethodsSuspension bead arrays targeting 124 unique proteins with antibodies from the Human Protein Atlas were used to profile biotinylated serum samples. Discoveries from a cohort of 77 individuals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 32 publications
2
3
0
1
Order By: Relevance
“…As previously reported, SHKBP1 protein expression in the serum of patients with primary neuroendocrine tumor, lymph node metastasis, and liver metastasis was significantly elevated compared with healthy individual’s serum. 43 The expression of linear SHKBP1 was not upregulated in GECs, inferring that circ-SHKBP1 and linear SHKBP1 are two mutually independent RNA and might perform different functions, which is consistent with the role of circ-TTBK2 and circ-HIPK3. 41 , 44 …”
Section: Discussionsupporting
confidence: 59%
“…As previously reported, SHKBP1 protein expression in the serum of patients with primary neuroendocrine tumor, lymph node metastasis, and liver metastasis was significantly elevated compared with healthy individual’s serum. 43 The expression of linear SHKBP1 was not upregulated in GECs, inferring that circ-SHKBP1 and linear SHKBP1 are two mutually independent RNA and might perform different functions, which is consistent with the role of circ-TTBK2 and circ-HIPK3. 41 , 44 …”
Section: Discussionsupporting
confidence: 59%
“…As for its downstream signaling pathway, miR-499a was found targeting SHKBP1. Studies showed that compared with healthy individual’s serum, SHKBP1 protein expression in the serum of patients with lymph node metastasis and liver metastasis was significantly elevated [36], but studies on the regulating mechanisms SHKBP1 is few. Here, we unveiled that TGFβ-induced EMT in CD166 + OSCs results in decreased miR-499a and enhaced SHKBP1 expression level.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the cell models used here, it emerges the idea about the relevance of KCTD5 in cancer. Several members of the KCTD protein family are linked to different types of cancer [ 30 , 32 , 40 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ]. Moreover, migratory features acquisition is crucial for malignant cells spread from localized tumors to distant organs [ 75 ].…”
Section: Discussionmentioning
confidence: 99%